Pelatihan Pembelajaran dan Penilaian Berbasis Literasi untuk Guru Mata Pelajaran IPS Kabupaten Lamongan: Pengabdian - Segara, Nuansa Bayu; Utami, Wiwik Sri; Harmanto, Harmanto; Prabawati, Indah; Wisnu, Wisnu; Purnomo, Nugroho Hari; Meirinawati, Meirinawati; Mudzakkir, Moh.; Afifah, Silvi Nur; Huda, Mi'rojul (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Program (PKM) aims to enhance the pedagogical competence of Social Studies (IPS) teachers in Lamongan Regency in implementing literacy-based learning and assessment. The program was initiated in response to teachers’ limited understanding of comprehensive literacy concepts and their challenges in designing learning strategies and authentic assessment tools that measure students’ critical thinking skills. The activity was conducted through workshops and sharing sessions using participatory approaches, including interactive lectures, group discussions, and practical sessions on designing literacy-based lesson plans and assessment instruments. The results indicate a significant improvement in teachers’ understanding and ability to apply literacy principles in Social Studies instruction. Most participants were able to identify literacy elements, design learning activities that promote critical thinking, and develop authentic literacy-based assessment tools. Furthermore, the training fostered collaboration among teachers through the MGMP as a sustainable professional learning community. Overall, this program contributes to improving the quality of Social Studies learning in Lamongan Regency and serves as a best practice model that can be replicated in other regions.